Eyetrackingowe badanie weryfikacyjne procesu czytania u dzieci ryzyka dysleksji – analiza przypadków - Marzena Kowaluk-Romanek; Rafał Ireneusz Wawer (Problemy Wczesnej Edukacji)
The text presents an extract of an eye tracking verification study of the reading process in children with the risk of dyslexia. A case study analysis was used. The study revealed differences and irregularities between children with the risk of dyslexia and their peers in areas such as: number of fixations, length of fixations and length of observation of text. It was observed that the intensity of difficulties associated with the reading skills does not have to be proportional to the irregularities of the movements of the eye balls (for instance, serious decrease in the reading skills with insignificant improper movements of the eyes) but visual perception of the text being processed varies, which is graphically presented in the text.